PENINGKATAN ADAPTASI TEKNOLOGI DAN INFORMASI KEPADA TENAGA KEPENDIDIKAN SEKOLAH MELALUI PROGRAM KAMPUS MENGAJAR - Gusti Eva Tavita; Amriani Amir; Asri Mulya Ashari; Riza Linda; Rita Kurnia Apindiati (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: The creativity and innovation of teachers in learning methods and techniques is very important in the success of the learning process of students in the classroom. The use of technology to accommodate the creativity of education personnel has become a basic need, and to make this happen, requires intensive assistance and training. The purpose of this activity is to examine the application of technology adaptation to education staff at the state elementary school No. 15 Segedong, Bengkayang Regency, West Kalimantan, through the students of the Teaching Campus 2 (KM 2) team assigned to the school. This research is descriptive qualitative, using primary data sourced from field observations, interviews with education staff (school teachers), school principals and students who become KM 2 agents at the school accompanied by documentation that supports factual activities in the field. In addition, this research is also supported by the availability of secondary data that can be obtained from the literature or references that are relevant to the research topic. The results showed that the technological adaptation carried out by the students of the KM 2 Segedong team went well, and could improve the ability of the educators at the school in utilizing science and technology (IT) in learning methods at the school. Keywords : Technology Adaptation; Campus Teaching; Creativity; Learning Methods